(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT The purpose of this study was to determine the effect of human resource competence of the effectiveness of public service district governments Ratatotok Southeast Minahasa Regency. This study uses quantitative methods. Research was carried by 30 votes apparatus (PNS) Ratatotok the District government. Instruments and data collection techniques used are questionnaires and aided by structured interview (interview quide). The analysis technique used to test the hypothesis is simple statistical regression analysis and simple correlation or correlation product moment. The results of data analysis provides conclusions: (1) Based on a simple regression analysis that the competency of HR personnel have functional relations / positive and significant impact on the effectiveness of public services at the sub-district office Ratatotok Southeast Minahasa Regency. This means that the higher / better human resource competence of the better / higher the level of effectiveness of public services. (2) Based on product moment correlation analysis that the competence of human resource to correlate and power of determination / significant influence on the effectiveness of public services at the sub-district office Ratatotok Southeast Minahasa Regency. This means that the competence of human resource is the dominant factor in deciding the effectiveness of public services; that the absence of adequate human resource competencies it is difficult to expect the effectiveness of public services can be realized optimally. Based on the results of this study, it can be recommended some of the following: (1) To improve the effectiveness of public services in the sub-district office Ratatotok the competence of human resource / staff should be improved, especially technical competence / functional. For that to the officers / employees let be given education and training (training), especially technical training / functional right or in accordance with the needs and field assignments / positions these employees. (2) Given the districts is the spearhead of the district government, the public service in the sub-district office personnel stationed let / employees who have sufficient competence. This is necessary because the reality shows that employees are generally placed in the sub-district office is a new employee or recently lifted (inexperienced) and inadequate education. Keywords: human resource competence, effectiveness of public services.